Socio-economic and agricultural potential of cattle manure application for crop production in Uganda - Muhereza, Innocent (Curtin University, 2012)
Declining soil fertility coupled with minimal nutrient inputs have contributed to low crop yields in sub-Saharan Africa; a major constraint to food security and economic development in Uganda. The use of cattle manure in agriculture is increasing as an alternative source of fertiliser and as a means of increasing or preserving soil organic matter. Research presented in this thesis was undertaken to: identify socio-economic issues affecting the use of cattle manure and inorganic fertiliser in Uganda; determine the crop response of Brassica spp to cattle manure as a source of N compared to inorganic N; and model the response of Brassica spp to applications of N from cattle manure and/or inorganic fertiliser for two major agroecological zones; dry land agriculture in Western Australia and tropical peri-urban agriculture in Uganda. The socio economic, agronomic and environmental viewpoints were considered. A survey conducted in Uganda as part of this study, highlighted that fifty-five percent (55%) of respondents reported that cattle manure was not adequate to fertilize the whole farm in a single cropping season due to the few animals kept on limited land of 0.2 ha- 0.8 ha or inadequate fodder as reported by 88% and 69%, respectively. A number of challenges associated with cattle manure use included weight and bulkiness of manure (75%), lack of labour (68%), high transportation and application costs (38%) and lack of storage facilities (33%) to maintain quality attributes of manure.The quality attributes of cattle manure for canola (Brassica napus) production were investigated further using manure stored for four months (M4) (1.31% N) and twelve months (M12) (0.32-1.18% N) compared with inorganic N (urea 46% N) on light textured sandy soil, using different rates following a systematic experimental design. Cattle manure was obtained from a cattle feedlot at Ucarty 120 km East of Perth, Western Australia and used in two field experiments whereas urea as a source of N was used in both field and glasshouse experiments. The cattle manure N was predominantly organic, and hence the inorganic fraction available for crop uptake at all times was extremely low.The growth response of canola (Brassica napus) to increasing rates of cattle manure and comparable rates of inorganic N as urea, to a maximum of 200 kg ha-1 was examined in the field for two growing seasons to determine a N response curve. Fresh and dry weight yields and N uptake in relation to organic N from cattle manure were statistically analysed by linear regression analysis and compared to respective yields from mineral N calibration plots. Linear models of the form y = a + bx were fitted to the data where y is the yield (kg ha-1 fresh or DM or N uptake).The percentage relative effectiveness (RE) was calculated for seasonal DM production and N uptake in canola during the 2009 and 2010 growing seasons. In the first year of canola, the RE for N uptake in cattle manure compared with top-dressed inorganic N ranged from 13% to 18% over the season and by harvest DM was 22%. In the second year, the RE for N uptake by canola in cattle manure averaged 28% for M4 and 21% for M12 over the growing season compared with top-dressed inorganic N, and by harvest, the RE of DM was 33% for M4 and 26% for M12. Urea was more effective as a source of N than comparable N loadings for either M4 or M12 as indicated by RE for fresh weight, DM and N uptake. Factors such as low mineralisation rate of N contributed to the lower effectiveness of cattle manure N under field conditions.The progressive increases in RE in stored cattle manure may be due to a number of factors including N in cattle manure becoming more available with time, the manure N being accessed more effectively by larger plant roots, increased soil moisture and or higher rates of N responding to lower levels of soil N. There was no evidence to suggest that lower soil N contributed to improvement in percentage RE during the season since soil tests were not conducted after the conclusion of the experiments.Dry cattle manure at 62 tonnes ha-1 of M12 and 44 tonnes ha-1of M4 would be required to achieve high potential yield. The calibrated computer model predicted the response of canola to N availability and quantified potential yield of canola under cattle manure and inorganic fertiliser application. The model was then adapted to high yield potential soils of Uganda and showed yield increases and returns from N additions on simulated potential yields of cabbage and other factors for crop growth to be constant. Maximum returns of A$3,041, A$3,518 and A$4,230 ha-1 would be obtained under manure N application rates of 360, 440 and 600 kg N ha-1 at a cost of A$1,188, A$1,452 and A$1,980, respectively. The cost of N would be A$800, A$960 and A$1,280 ha-1 under inorganic N at optimal levels at maximum returns of A$3,970, A$4,721 and A$5,837 ha-1 for low, medium and high potential yield, respectively.The growth response of Brassica species including two cabbage varieties and canola was examined in the glasshouse. There were no growth differences among the three Brassica spp grown in adequate N, indicating that the canola model may be a suitable proxy for modelling cabbage production when it comes to N application response.The model took into account rainfall, which in the first year season increased the maximum depth of the wetting front by about 46 cm resulting in N leaching further below the root zone as opposed to the second year.Final rooting depth was less with lower rainfall and increased rainfall significantly reduced nitrate in the rooting zone in the weeks in which the rainfall occured due to increased leaching.Based on the experiments conducted and the socio-economic survey, the research addressed the problem of soil fertility decline in sub-Saharan Africa, particularly in Uganda. It identified constraints to fertiliser use for crop production in peri-urban agriculture in Uganda, focusing on the use of cattle manure and/or inorganic N fertiliser. A bio-economic model developed predicted N fertiliser requirements to improve crop yields and economic returns for cabbage production. The thesis findings will contribute towards improved cattle manure utilisation in agriculture in sub-Saharan Africa. Although the research primarily investigated dry solid cattle manure applied to dryland agriculture in Western Australian soils, the results will be of relevance to any farming system involved in the land application of cattle manure, to increase food production and to make better use of N in crop production.Further studies are required in Uganda to determine and verify the key coefficients in the bio-economic model before it can be used to make recommendations. This should include other N sources including cow’s urine, poultry manure and goat manure.